Pengaruh Pengadopsian XBRL terhadap Asimetri Informasi dengan CG sebagai Variabel Moderasi - Dewi Purnama Sari; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2021)
This study investigates the impact of Exstensible Business Reporting Language (XBRL) adoption on information asymmetry, with Corporate Governance (CG) as moderating variabel. The purpose of this study was to analyze : (1) The impact of adoption XBRL on information asymmetry, (2) The impact of CG as moderating variable to strengthen impact of XBRL on information asymmetry. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The sample selection technique used in this study was purposive sampling technique. The research samples used 59 companies with observation sample was 259 samples. Methods of data analysis using eview9. The results of the study found that : (1) XBRL has a insignificant effect with a result of 0.232> 0.05, (2) GCG has a insignificant effect in moderating the XBRL relationship to information asymmetry with results 0.2833> 0.05.